The Effect of Providing Infrared and Breathing Exercise: Breathing Control & Thoracic Expansion Exercise on Pulmonary Empyema Patients in dr. Ario Wirawan Lung Hospital in Salatiga - Sujak, Rhama Syuhada; Widodo, Agus; Lestari, Ririt Ika (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Pulmonary empyema is defined as a collection of pus in the pleural cavity, commonly with gram positive bacteria, or changes in pleural fluid. Empyema is usually associated with pneumonia but can also occur following thoracic surgery or thoracic trauma. In America, there are around 32,000 cases per year. Empyema is associated with increased morbidity and mortality, approximately 20% to 30% of affected patients will die or require further surgery in the first year after experiencing empyema. The percentage of morbidity and mortality from empyema is so high, the author is interested in making empyema into a case report paper. Case Presentation: The research method used in this research is a case report study of three physiotherapy interventions on 21 December 2023, 22 December 2023, and December 27 2023 followed by home exercise education for the patient's family. The intervention is carried out from the first meeting until the patient returns home from the inpatient ward. With the following clinical status: patient Mr. A. A. is 54 years old and works as an entrepreneur with a diagnosis of left thoracic empyema and was asked for a referral for physiotherapy by a thoracic surgeon. The patient complained of chest pain when carrying out heavy activities, coughing and WSD incisional chest pain. After intensive treatment, on December 17 2023 the patient was referred to physiotherapy for intervention. Management and Outcome: Physiotherapy care in the inpatient ward for pulmonary empyema patients was carried out from 18 December 2023 to 27 December 2023. Then they underwent infrared intervention, breathing exercise therapy: breathing control & thoracic expansion exercise. Then it was found that there was an evaluation of lung functional improvement in terms of reducing pain and reducing shortness of breath. Discussion: From three meetings with the same three interventions, more evaluation and physiotherapy procedures are needed to minimize bias in increasing functional breathing capacity, reducing pain and reducing shortness of breath. Drug therapy needs to be given to support the patient's recovery in the form of Cefixime to prevent infection, and Ibuprofen as an anti-inflammatory to prevent reacting of bacteria. In this case, patient was given home medication Cefixime 2x100mg and Ibuprofen 2x4000mg. Conclusion: In pulmonary empyema patients, the provision of breathing exercise physiotherapy interventions: breathing control & thoracic expansion exercise was evaluated to reduce pain during inspiration and was able to reduce the scale of shortness of breath.